Frequency and types of chromosomal abnormalities in acute lymphoblastic leukemia patients in Turkey - Osman Demirhana; Nilgün Tanrıverdia; Dilara Süleymanovaa (Archives of Community Medicine and Public Health - Peertechz Publications, 2019)
Objectives: Acute lymphoblastic leukemia (ALL) is the most common malignancy in children and is usually associated with numerical and structural chromosomal changes. The correlations of specifi c cytogenetic fi ndings with presenting clinical features indicate the prognostic signifi cance of chromosomal abnormalities (CAs) in patients with ALL. Design and methods: The aim of this study was to describe the types and frequencies of CAs in the childhood and adult ALL patients. To date, his was the largest study to date in of children with ALL in Turkey, and presented the general cytogenetic characteristics of 260 patients diagnosed as having with ALL in a 17-year period. The cytogenetic analyses were performed in the diagnosis of ALL patients.